2014
DOI: 10.5812/ircmj.13506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-regulation Training on Management of Type 2 Diabetes

Abstract: Background:Diabetes is the most common metabolic disorder which is required to be taken under control. According to some studies, the impact of self-regulation on health has been considered as a monitoring strategy to achieve individual’s goals.Objectives:This study, which was performed in 2012, aimed at determining the consequences of self-regulation on controlling type 2 diabetes.Patients and Methods:In this double-blind clinical trial, 60 patients with type 2 diabetes - who were referred to Diabetes Clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…All eligible articles had been published between January 2009 and March 2017. Of the twenty-three included studies, eleven (47.8%) were published in English [22][23][24][25][36][37][38][39][40][41][42], and the rests were published in Persian. Characteristics of the included studies can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All eligible articles had been published between January 2009 and March 2017. Of the twenty-three included studies, eleven (47.8%) were published in English [22][23][24][25][36][37][38][39][40][41][42], and the rests were published in Persian. Characteristics of the included studies can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the nature of the intervention, blinding of participants and educators was not feasible. The methodological quality of studies ranged from good to poor, with two studies (8.7%) were classified as being of good quality [22,23], and nine (39.1%) were of moderate quality [24][25][26][27][28][29][30][31][32]. The remaining twelve studies (52.2%) were of poor quality.…”
Section: No Diabetes Related Outcomes (N=10)mentioning
confidence: 99%
“…A review of qualitative studies highlighted the importance of self‐regulation for treatment adherence (Kelly et al, 2014 ). In addition, improving self‐regulation has been shown to help improve disease management in patients with diabetes (Tavakolizadeh et al, 2014 ). In the process of self‐regulation and behaviour change, health care providers need to know how to help patients develop skills to take control of their condition.…”
Section: Discussionmentioning
confidence: 99%
“…While similar situations are experienced in some countries, some made considerable progress in treatment and prevention with training and new regulations. Tavakolizadeh et al (13) showed that the blood sugar levels of diabetic patients significantly decreases after training and that their diet and exercise habits changed in a positive way.…”
Section: Discussionmentioning
confidence: 99%